Fabrication and Characterization of Chitosan–Vitamin C–Lactic Acid Composite Membrane for Potential Skin Tissue Engineering - Ahmed Madni; Romana Khan; Muhammad Ikram; Syeda Sohaila Naz; Taous Khan; Fazli Wahid (International Journal of Polymer Science)
Recent advances in tissue engineering have potential for the development of improved substitutes for damaged skin tissues. Vitamin C and lactic acid are well-known wound healing accelerators while chitosan is an important biomaterial having wound healing capabilities. However, addition of vitamin C induces fragility to the chitosan–lactic acid membranes. Therefore, the current study was designed to fabricate an intact chitosan–vitamin C–lactic acid composite membrane that may synergize the critical properties of every individual component for potential skin tissue engineering. For this purpose, different concentrations of glycerol and polyethylene glycol (PEG) were added to strengthen the chitosan–vitamin C–lactic acid membranes. The prepared membranes were characterized by Fourier transform infrared spectroscopy, X–ray diffraction, and field emission scanning electron microscopy. Moreover, the biocompatibility of the prepared membranes was evaluated with fibroblast NIH 3T3 cells. The results showed that addition of glycerol and PEG has improved the strength of chitosan–vitamin C–lactic acid composite membrane. Characterization studies revealed the successful synthesis of chitosan–vitamin C–lactic acid composite membrane. Moreover, the prepared membranes showed excellent biocompatibility with NIH 3T3 cells. However, it is important to note that cells showed more attachment and spreading on porous chitosan composites membranes as compared to nonporous membranes. This study provided a base for the development of an intact chitosan–vitamin C–lactic acid composite membrane for skin tissue engineering. However, further preclinical and clinical studies are required for its practical applications in skin tissue engineering.